Smart Air Humidifier For Air-conditioned Rooms Based On NodeMCU ESP8266 - Yudithia, Frenzi Agres; Herda, Deri Latika; Wahyudi, Al Hafizh (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
The advent of smart technology has significantly revolutionized home appliance management, with notable advancements including the development of smart air humidifiers. This paper delves into the design, implementation, and performance evaluation of an advanced air humidifier specifically engineered for air-conditioned environments, emphasizing its integration with mobile phone technology. The innovative device incorporates the NodeMCU ESP8266 microcontroller, which facilitates Wi-Fi connectivity, and the DHT22 sensor, known for its precise temperature and humidity measurements. Key features of this humidifier include a Mist Maker that enhances humidity levels, an LCD display for real-time data visualization, and remote control capabilities via the Blynk app. Comparative performance testing of the DHT22 sensor against the HTC-1 Thermometer Hygrometer demonstrated high accuracy, with an average temperature error of 1.89% and a humidity error of 1.87%, resulting in accuracies of 98.11% and 98.13%, respectively. The humidifier effectively maintained desired humidity levels by toggling between on and off states within a 44% to 45% relative humidity range. This smart humidifier represents a significant leap forward in indoor climate management, offering superior user convenience and comfort. By harnessing modern microcontroller technology and advanced sensors, it delivers considerable improvements over traditional models, making it an invaluable tool for sustaining optimal indoor conditions in air-conditioned spaces.